Perceptions and practices of community pharmacists towards antimicrobial stewardship in the state of Selangor, Malaysia - Khan, Muhammad Umair; Ahmad Hassali, Mohamed Azmi; Ahmad, Akram; Elkalmi, Ramadan Mohamed Mahmod; Razi Zaidi, Syed Tabish; Dhingra, Sameer (PLOS (Public Library of Science), 2016)
Background